2016
DOI: 10.1111/jace.14443
|View full text |Cite
|
Sign up to set email alerts
|

Structural Evolution in Hollandite Solid Solutions Across the A‐Site Compositional Range from Ba1.33Ga2.66Ti5.34O16 to Cs1.33Ga1.33Ti6.67O16

Abstract: Hollandite solid solutions along the A‐site compositional range from the pure barium end‐member Ba1.33Ga2.66Ti5.34O16 to the pure cesium end‐member Cs1.33Ga1.33Ti6.67O16 have been synthesized using a solid‐state reaction technique. The crystal structure of the hollandite across the entire compositional range remained in the I4/m space group. Structural evolution was resolved by neutron diffraction, total scattering data, and density functional theory calculations. A trend of decreasing thermodynamic stability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 26 publications
4
24
0
Order By: Relevance
“…Again, the reported 1473 K temperature at which the cooling rate of melt processed samples started slowing was adopted as the equilibrium temperature. Equilibrium calculations using assessed thermochemical models and values predict the hollandite phase is stable for the experimental compositions of Amoroso et al, Xu et al, Aubin‐Chevaldonnet et al, and Costa et al (Table ).…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…Again, the reported 1473 K temperature at which the cooling rate of melt processed samples started slowing was adopted as the equilibrium temperature. Equilibrium calculations using assessed thermochemical models and values predict the hollandite phase is stable for the experimental compositions of Amoroso et al, Xu et al, Aubin‐Chevaldonnet et al, and Costa et al (Table ).…”
Section: Resultsmentioning
confidence: 93%
“…Ti‐substituted hollandite, one of the SYNROC phases, is an alternative candidate for Cs immobilization. In these waste forms, 137 Cs (and other constituent radionuclides, ie 137 Ba, 87 Rb) is incorporated into the crystalline structure . Notably, natural analogs of hollandite including ankagite are present in dolomitic marble in the Apuan Alps in Tuscany, Italy, which demonstrates the stability of the hollandite phase over geologic timescales of interest for nuclear waste immobilization.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…More recent work has demonstrated the stability of high Cs containing compositions. Structural studies demonstrated the higher Cs loading resulting in a framework expansion in the direction perpendicular to the tunnel axis due to the incorporation of the larger Cs ions, resulting in less distortion in the oxygen octahedra and a more symmetric structure [11,56]. Higher symmetry structures resulted in a more stable hollandite in terms of formation enthalpy with respect to their constituent oxides.…”
Section: Model Single Phase Materials: Interfacial Characteristicsmentioning
confidence: 99%